British Media Coverage of the Press Reform Debate Journalists Reporting Journalism - Ogbebor, Binakuromo (Springer International Publishing : Imprint: Palgrave Macmillan, 2020)
This open access book provides a detailed exploration of the British media coverage of the press reform debate that arose from the News of the World phone hacking scandal and the Leveson Inquiry. Gathering data from a content analysis of 870 news articles, Ogbebor shows how journalists cover debates on media policy and illustrates the impact of their coverage on democracy. Through this analysis, the book contributes to knowledge of paradigm repair strategies; public sphere; gatekeeping theory; the concept of journalism as an interpretive community; political economy of the press; as well as the neoliberal and social democratic interpretations of press freedom. Providing insight into factors inhibiting and aiding the role of the news media as a democratic public sphere, it will be a valuable resource for the press, media reform activists, members of the public, and academics in the fields of journalism, politics and law.